Cartilage tissue healing and regeneration based on biocompatible materials: a systematic review and bibliometric analysis from 1993 to 2022 - Yao, Meng-Xuan; Zhang, Yi-Fan; Liu, Wei; Wang, Hai-Cheng; Ren, Chuan; Zhang, Yu-Qin; Shi, Tai-Long; Chen, Wei (Frontiers in Pharmacology, 2024)
Cartilage, a type of connective tissue, plays a crucial role in supporting and cushioning the body, and damages or diseases affecting cartilage may result in pain and impaired joint function. In this regard, biocompatible materials are used in cartilage tissue healing and regeneration as scaffolds for new tissue growth, barriers to prevent infection and reduce inflammation, and deliver drugs or growth factors to the injury site. In this article, we perform a comprehensive bibliometric analysis of literature on cartilage tissue healing and regeneration based on biocompatible materials, including an overview of current research, identifying the most influential articles and authors, discussing prevailing topics and trends in this field, and summarizing future research directions.